Endogenous γ-aminobutyric Acid Modulates Tonic Guinea Pig Airway Tone and Propofol-induced Airway Smooth Muscle Relaxation - Gallos, George (2009)
BACKGROUND: Emerging evidence indicates that an endogenous autocrine/paracrine system involving γ-aminobutyric acid (GABA) is present in airways. GABA(A) channels, GABA(B) receptors and the enzyme that synthesizes GABA have been identified in airway epithelium and smooth muscle. However, the endogenous ligand itself, GABA, has not been measured in airway tissues. We sought to demonstrate that GABA is released in response to contractile agonists and tonically contributes a pro-relaxant component to contracted airway smooth muscle. METHODS: The amount and cellular localization of GABA in upper guinea pig airways under resting and contracted tone was determined by high pressure liquid chromatography and immunohistochemistry, respectively. The contribution that endogenous GABA imparts on the maintenance of airway smooth muscle acetylcholine-induced contraction was assessed in intact guinea pig airway tracheal rings using selective GABA(A) antagonism (gabazine) under resting or acetylcholine-contracted conditions. The ability of an allosteric agent (propofol) to relax a substance P-induced relaxation in an endogenous GABA-dependent manner was assessed. RESULTS: GABA levels increased and localized to airway smooth muscle following contractile stimuli in guinea pig upper airways. Acetylcholine-contracted guinea pig tracheal rings exhibited an increase in contracted force upon addition of the GABA(A) antagonist gabazine which was subsequently reversed by the addition of the GABA(A) agonist muscimol. Propofol dose-dependently relaxed a substance P contraction that was blocked by gabazine. CONCLUSION: These studies demonstrate that GABA is endogenously present and increases following contractile stimuli in guinea pig upper airways and that endogenous GABA contributes a tonic pro-relaxant component in the maintenance of airway smooth muscle tone.